1975
DOI: 10.1254/jjp.25.583
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Respiration of Guinea Pig Taenia Coli in High-K Medium; The Role of Nicotinamide-Adenine Dinucleotide, Adenosine Diphosphate and Ca++

Abstract: Abstract-In an attempt to elucidate the regulation mechanism of respiration in the smooth muscle cell, we investigated the roles of nicotinamide-adenine dinucleotide (NAD), adenosine diphosphate (ADP) and Ca" in the muscle respiration using the tissues and subcellular fractions from guinea pig taenia coli. The tension in the strips of taenia coli increased with a concomitant increase in 02 consumption in high-K medium (40 mM K) containing 2.5 mM Ca. 10-3 M amytal and 10-6 M ouabain decreased the high-K induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1977
1977
1999
1999

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
(15 reference statements)
2
3
0
Order By: Relevance
“…This effect of papaverine was consistent with that reported in other papers (20,21). Since BASS did not remarkedly inhibit the 60 mM K-induced tonic con traction, the action of BASS seems to be also different from that of papaverine which inhibits phosphodiesterase activity (22)(23)(24) or mitochondorial respiration (25,26).…”
Section: Discussionsupporting
confidence: 90%
“…This effect of papaverine was consistent with that reported in other papers (20,21). Since BASS did not remarkedly inhibit the 60 mM K-induced tonic con traction, the action of BASS seems to be also different from that of papaverine which inhibits phosphodiesterase activity (22)(23)(24) or mitochondorial respiration (25,26).…”
Section: Discussionsupporting
confidence: 90%
“…The essential role of NAD`.-linked respiration in the smooth muscle respiration in 40-K medium was reported previously (8). Moreover, the inhibition of Pap to the NADH-linked respiration reached a steady level within 1 min in both the homogenate and in the Mt of taenia coll.…”
Section: Property Of the Subcellular Fractionssupporting
confidence: 76%
“…Pigeon heart homogenate was centrifuged for 5 min at 600 x g to produce a supernatant which was centrifuged for 20 min at 12,000 x g to yield the resultant pellet that was centrifuged for 15 min at 5,500 x g. This pellet was used as the pigeon heart mitochondrial fraction. A taenia coli homogenate and Mt were also prepared using the Ultra-Turrax as reported previously (UT method) (8). All procedures were performed at low temperatures (W-4`Q.…”
Section: Methodsmentioning
confidence: 99%
“…Pap at 5,,1,10-5 M inhibited the increased Qo2 and tension simultaneously, much the same as was seen with amytal (20). From the series of experiments concerning O2 consumption (20)(21)(22)(23), it is known that in the 40-K medium, the inhibition of increased Qo2 (IQo) is sufficient for the inhibition of developed tension (12e) but is not a necessary condition.…”
Section: It Was Reported Thatmentioning
confidence: 68%
“…, in each treatment. It was previously reported that the reduction of intracellular Call concentration inhibited both the smooth muscle tension and the muscle respiration, and that the reduction of ATP utilization also inhibited Qo2 (20). However, these inhibitions of Qo2 were fully antagonized by DNP (20).…”
Section: It Was Reported Thatmentioning
confidence: 92%